Northern Fowl Mite - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler; Harvey L. Cromroy (EDIS)
The northern fowl mite (Figure 1) is the most important external parasite of poultry in Florida and is widely distributed throughout the state. This mite is found throughout many of the temperate regions of the world parasitizing domestic fowl and wild birds. It has been shown to cause economic damage on poultry farms by causing anemia, lower egg production and even death to birds. Also of considerable importance, the mites will bite man (egg handlers) causing itching and irritation to the skin. This document is ENY-286 (IG141), one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Originally published as Livestock Protection Pointer Number 3, August 1978. Revised March 2006.